Catheter directed thrombolysis terapi emboli paru pada ibu hamil - Maurizka, Aulia Dita (Wellness And Healthy Magazine, 2020)
The incidence of pulmonary embolism in developing countries is increasing every day. Pulmonary embolism is a life-threatening emergency. The incidence of pulmonary embolism is related to physiological conditions of pregnant women where there is an increase in coagulation factors such as factors I, II, VII, VIII, IX, X, increase in fibrin and protein S. This causes pregnant women to be more susceptible to stasis venous thromboembolism become Deep Vein Thrombosis and if it continues to become a life-threatening pulmonary embolism. Therapy in pulmonary embolism is still emphasized by the use of thrombolytics to destroy the thrombus. However, based on research in the last few years, it was found that serious complications due to the use of thrombolytics such as bleeding, abortion, and even maternal death. Therefore a new method was formed in the form of a Catheter Directed Thrombolysis (CDT), which was able to reduce the risk of bleeding in pregnant women with pulmonary embolism so that they could get good results. CDT is a minimal intervention therapy by inserting a catheter into the body until it approaches the thrombus in the lungs, then removing thrombolysis agents around the thrombus in the hope of thrombus lysis and not occurring hemodynamic disorders.